Topographic Relationship with a Retinal Nerve Fiber Layer Defect Differs between β-Zone and γ-Zone Parapapillary Atrophy - Eun Hye Jung; Eun Ji Lee; Tae-Woo Kim (Journal of Ophthalmology, 2020)
Introduction. γ-Zone parapapillary atrophy (PPA), an associated feature in myopic tilted optic disc, is considered to be relevant with glaucomatous optic nerve damage in myopic eyes. This study determines the topographic relationship of γ-zone PPA with a retinal nerve fiber layer defect. Purpose. To determine the topographic relationship of γ-zone PPA with a RNFL defect and to compare it with that of β-zone PPA. Design. Cross-sectional, observational study. Participants. Eighty-nine eyes from 89 patients with primary open-angle glaucoma who had β-zone PPA (n = 49) or γ-zone PPA (n = 40) and a single localized RNFL defect. Methods. PPA was classified according to the presence or absence of Bruch’s membrane on the PPA bed in spectral-domain optical coherence tomography. The angular location of the point of maximum radial extent of PPA (PMRE) and the RNFL defect was measured with the fovea-disc axis set at 0° in color and red-free fundus photographs. Main Outcome Measures. Angular distance between the RNFL defect and the PMRE. Results. There was no significant intergroup difference in the extent of the RNFL defect (P=0.920). The angular distance between the RNFL defect and the PMRE was significantly greater in γ-zone than β-zone PPA (26.49 ± 17.27° vs. 60.31 ± 17.12°, P<0.001). The angular location of the PMRE was significantly correlated with the location of the RNFL defect in the β-zone group (r = 0.822, P<0.001) but not in the γ-zone group. The RNFL defect was mostly located near the edge of γ-zone PPA in the γ-zone group (10.56 ± 9.47°). Conclusions. An RNFL defect was observed near the edge of PPA in eyes with γ-zone PPA, in contrast to it being close to the PMRE in eyes with β-zone PPA.